The factors which influence exclusive breastfeeding on toddlers in North Minahasa regency, North Sulawesi - Punuh, Maureen I.; Engkeng, Sulaemana (International Journal Of Community Medicine And Public Health, 2021)
Background: Exclusive breastfeeding is the process of giving breast milk to babies without any additional food from birth until they are six months old. It takes the role of mothers, health workers and families, especially husbands so that exclusive breastfeeding can be successful. The purpose of this study was to determine the factors associated with exclusive breastfeeding for children in North Minahasa regency Methods: This study used a cross sectional design on 132 toddlers aged 7-12 months. The sampling in this study was carried out by using purposive sampling technique. Results: The results of the study found that 44.7% of children under five received exclusive breastfeeding and 25.0% of children had early initiation of breastfeeding from their mother. From this study it is also known that 55.3% of mothers’ knowledge level about exclusive breastfeeding is in the sufficient category, 52.3% of health workers have a good role and as many as 54.5% of husbands play a good role in exclusive breastfeeding. Conclusions: The results obtained based on statistical tests using chi square were there is association of early initiation of breastfeeding (p=0.018), knowledge about exclusive breastfeeding (p=0.045), the role of health workers (p=0.030), and the role of husband on the exclusive breastfeeding for children in North Minahasa regency. However, maternal knowledge and supervision regarding the early initiation of breastfeeding and health workers needs to be more improved.